Study of the complexation between Landomycin A and C60 fullerene in aqueous solution. Issue 84 (26th August 2016) - Prylutskyy, Yu I.; Cherepanov, V. V.; Kostjukov, V. V.; Evstigneev, M. P.; Kyzyma, O. A.; Bulavin, L. A.; Ivankov, O.; Davidenko, N. A.; Ritter, U.
Abstract : We report here the first investigation of the non-covalent complexation between C60 fullerene and angucycline antibiotic Landomycin A. Abstract : We report here the first investigation of the non-covalent complexation between C60 fullerene and angucycline antibiotic Landomycin A. By means of various physico-chemical methods, including atomic force microscopy, dynamic light scattering, ζ -potential, small-angle neutron scattering and molecular modelling, it was shown that the obtained experimental data indirectly evidence complexation. This result provides scientific reasoning for further examination of the possible biological interaction between these agents on simultaneous administration in vivo and in vitro .